Long-term disease-free survival of a patient of acute myeloid leukemia with superior vena cava syndrome grade 2 with adjunct Ayurvedic treatment: A case report - Sadanand Sardeshmukh; Vineeta Deshmukh; Arvind Kulkarni; Vasanti Godse; Shrinivas Datar; Swapna Kulkarni; Sushama Bhuvad; Anita Shingte; Sandeep Chavan (Journal of Ayurveda and Integrative Medicine)
Long-term disease-free survival (DFS) of 19 years and 8 months is achieved in an Indian male young patient with Acute Myeloid Leukemia (AML) with a grade 2 Superior Vena Cava (SVC) syndrome treated with chemotherapy and adjunct personalized Ayurvedic treatment with medicines having antipyretic (Jwaraghna), reduces inflammation and swelling (Shothaghna) and rejuvenating (Rasayana) properties and effective in anemia (Pandu) and respiratory diseases (Diseases of pranavaha srotasa)In January 2002, this patient was diagnosed with Pulmonary Kochs and Anti Koch's treatment was given for 6 months. However, due to persistent low-grade fever and supra clavicular lymph node enlargement, he was further investigated with X-Ray Chest in July 2002 revealing mediastinal lymphadenopathy with Right Costophrenic angle pleural effusion. (Grade 2 SVC syndrome). Histopathological report of Supraclavicular Lymph node confirmed the hematolymphoid possibility of acute leukemia. He underwent an aggressive course of chemotherapy from August 2002 to October 2003. Initially four Cycles of Oral Chemotherapy (Tab. Mercaptopurine 100 mg with Cap. Etoposide 100 mg) were administered instead of IV Chemo during the period of August 08, 2002 to December 02, 2002 due to financial problem of patient. Thereafter he was treated with two cycles of consolidation with Inj. Cytarabine (high dose) from December 05, 2002 to January 31, 2003 followed by four cycles of maintenance chemotherapy (Inj. Daunomycin 90 mg and Cytarabine high dose 190 mg) from February 06, 2003 to May 07, 2003 and again four cycles of oral chemotherapy from May 26, 2003 to October 07, 2003 (Tab 6 TG (40 mg) 2 tablets and Cap Posid 100 mg OD for 21 days)The patient started Oral Ayurvedic Medicines (OAM) in August 2002 i.e. at the beginning of chemotherapy which consisted of 3 sets of herbo-mineral Ayurvedic medicines to minimize the side effects of chemotherapy, prevent anemia, and bleeding disorders, strengthen the respiratory system as well as boost immunity to prevent disease recurrence. Since his all pathological parameters were normal and his quality of life was improved significantly, Ayurvedic treatment was stopped in Nov 2008 and he was kept under follow-up. He is asymptomatic without any disease recurrence to date.In this case of AML having grade 2 SVC syndrome with unfavorable prognostic factors as male sex, diagnosis at 24 yrs. age, low socioeconomical status and also with limited life expectancy, a long-term DFS of 19 years and 8 months is reported. It has been achieved by an integrative approach of chemotherapy and personalized adjunct Ayurvedic treatment consisting oral herbo-mineral medicines.